Analysis of biomimetic hierarchical porous structure regulating radiation field to improve solar thermochemical performance based on minimum Gibbs free energy. (15th January 2022) - Shi, Xuhang; Xun, Yimeng; Dong, Yan; Wang, Fuqiang; Zhang, Xinping; Cheng, Ziming
Abstract: Solar energy is the source of energy required for the dry methane reforming (DMR). In the high temperature field induced by concentrated solar energy, the spatial distribution of radiation intensity has a significant impact on the solar thermochemical performance. Based on principle of minimum Gibbs free energy ( G min ), the idea of regulating radiation field to match solar thermochemical energy conversion on-demand is proposed. To improve solar thermochemical conversion efficiency, biomimetic hierarchical porous structure is introduced as solar thermochemical reactor, which can optimize both the radiation field and temperature field. The analysis model of solar driven DRM is established, combined with user-defined functions (UDFs). The effects of pore diameter combinations along the direction of L and R on the reforming properties are studied. The results show that by designing biomimetic hierarchical porous structure, the temperature of solar thermochemical reactor can approach the thermodynamic temperature (1050 K), and finally the methane conversion is improved by up to 7%. Highlights: Based on G min principle, DMR in biomimetic solar thermochemical reactor is studied. Idea of regulating radiation field to match energy conversion on-demand is proposed. Biomimetic hierarchical porous structure is introduced to optimize temperature field. Optimized temperature is close to 1050 K, methane conversion is improved by 7.0%.